Pelatihan Supervisi Berbasis Kategori Guru Bagi Kepala Sekolah Dasar Kota Solok - Rifma Rifma; Rusdinal Rusdinal; Sufyarma Marsidin; Ranti Meizatri (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Efforts to improve and improve the quality of the learning process cannot be separated from the role of professional teachers and principals. In the context of efforts to improve the quality of educational resources, especially teachers, it is necessary to carry out programmed and continuous supervision by school principals who also have competence in carrying out supervision. The purpose of this training is to provide knowledge and skills to school principals in implementing teacher category-based supervision. The method of implementing this training is through lectures, discussions, case studies, and assignment methods (recitation). Supervision competency improvement training in this proposal is grouped into 2 major activities, namely the delivery of material and guided assignments. Supervised assignments are carried out for three months after the training is given. In this guided assignment the school principal implements the supervision program documents that have been prepared at the training stage. During its implementation, the principal is guided by the service team and resource persons with an agreed schedule. Activity evaluation is carried out 3 times, namely before the main activity, during the process, and after the activity. Evaluation prior to core activities is carried out in the form of a pre-test. The results of the Pre-test and Post-Test of Solok city school principals showed that there was an increase in the principal's understanding of 27.5% in the aspects of: (1) supervisory competence, (2) understanding of curriculum content, approaches, and assessment based on literacy and numeracy, and (3) understanding related to the psychology of communication in the implementation of supervision.